Quality of life outcomes one year after replacement of the temporomandibular joint using a modified SF36 questionnaire. Issue 3 (April 2020) - Gupta, B.; Ahmed, N.; Sidebottom, A.J.
Abstract: The aim of this study was to assess the quality of life (QoL) of patients who had total replacement of the temporomandibular joint (TMJ) using a modified short form 36 (SF36) questionnaire, which is validated for use in this context. A total of 36 patients (32 female, 4 male, mean (range) age at the time of operation 44.5 (19-74) years) who had TMJ replacements between 2013 and 2016 were evaluated. Each completed a questionnaire preoperatively and at one year postoperatively. Postoperatively there were significant reductions in scores for pain and anxiety, and improvements in mood, diet, and the ability to chew. There were no significant differences between the preoperative and postoperative scores in terms of speech or recreation, although most reported an overall improvement in general well-being. Our results suggest that TMJ replacement is associated with a better QoL in terms of pain and function, and that the modified questionnaire is suitable for the appraisal of outcomes after this type of operation.